Estimation of Adenosine Deaminase in Adult Iraqi Patients with β-Thalassemia - Hassanain K. Al-Bairmani (Journal of Global Pharma Technology, 2018)
Beta-thalassemia is a well-known hereditary hemoglobinopathy. Patients with major and intermedia thalassemia require periodic blood transfusions. The diagnosis of this disease involves the investigation of several biochemical and hematological markers. Adenosine deaminase (ADA) has received much attention due to its role in purine catabolism, and in this work the activity of ADA was estimated among two patient groups of thalassemia (major and intermedia) and control group. A significant increase was found in studied groups as compared with control group. The levels of Iron, ferritin, transferrin, ALT and AST were also estimated in the current study. It was found that the levels of these parameters were correlated with the activity of ADA.Keywords:  Beta-thalassemia; Adenosine deaminase; ALT; AST